UZBEK LEARNERS' OPINIONS ON THE EFFECT OF DIALECT AND CULTURAL SIMILARITY ON THE PROCESS OF FOREIGN LANGUAGE LEARNING - Albayrak, Fatma; Serin, Nilüfer (International Online Journal of Education and Teaching, 2022)
The aim of this research is to determine the effect of Uzbeks' views towards Turkish language and Turkish culture on language learning processes. In the study, which was designed according to the qualitative research model, a semi-structured interview form was used as a data collection tool. Interviews were held with 33 B1-level Uzbek learners who study Turkish language in language teaching centers affiliated to higher education institutions in Turkey.After the data obtained through semi-structured interviews were transcribed, the researchers carried out coding, categorization and classification according to themes on the raw data. According to the results of the study, it was revealed that Uzbek learners generally had a positive perception of Turkish language learning processes, life in Turkey and Turkish culture, and this situation was directly related to the perception that Turkey provided historical closeness, religion, language, cultural similarity and quality education and life opportunities in today's conditions for Uzbeks.In addition, it was seen that learners developed a positive attitude towards learning because they thought that they were advantageous as speakers of the same language dialects in the language learning process, and they also supported their positive view of language with the facilitating effect of vocabulary and grammatical similarity